Proximate and Texture Profile Analysis of Gluten-Free Cookies Made from Black Glutinous Rice and Mung Bean Flour - Putri, Soraya Kusuma; Setiyoko, Agus (Universitas Ahmad Dahlan, 2025)
Cookies are one of the food product kinds that have been extensively studied as low-calorie and high-fiber foods. Non-gluten cookies (high fiber) could be made with black glutinous flour and mung bean flour. Black glutinous rice is a valuable ingredient to enhance dietary fiber and antioxidants in food products. The mung bean flour had significant levels of crude fiber (3.77%), iron (89.62 mg), and protein (18.42%). This substance was chosen because mung bean flour and black glutinous rice flour are gluten-free flour, and this research contributed to diversifying food beyond grains and cereal and analyzing that physicochemical profile. This study offers to determine the differences between the findings of proximate analysis and texture profile analysis in cookies made using mung bean flour and black glutinous rice flour. The composite of flour was made from mung black glutinous rice flour and mung bean (F1 = 0:100; F2 = 30:70; F3 = 70:30; F4 = 100:0). The experiment used a completely randomized design to compare the physicochemical and profile texture parameters of cookies. The result of this study is the highest proximate content in terms of protein is in F2, with a moisture content of 4.43%, ash content of 4.80, fat content of 9.46, and carbohydrate content of 73.32%, which is following the Indonesian National Standard (SNI) 01-2973-2022. The texture profile such as hardness 106.23 ± 0.12 N, cohesiveness 0.405 ± 0.17, springiness 0.84 ± 0.24, gumminess 53.54 ± 0.04, and chewiness 33.53 ± 0.02 N.